The influence of alī shīr navā’ī’s works on azerbaijan literature - TULKİN SULTANOV (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2023)
The literary relations of the Uzbek and Azerbaijani peoples, who have a common language, culture and traditions, reached their peak thanks to the literary legacy of Alisher Navoi. Alisher Navoi, one of the most important common figures of the Turkic World, is seen in the same level with famous artists in world literature such as Homer, Dante, Nizamî, Sa'di, Shakespeare, Balzac, Tolstoy and Tagor. Navoi is a great literary man who made important contributions to the development of Turkic language and literature. Alisher Navoi (1441-1501), the greatest figure of Chagatai Literature, which developed in Central Asia during the Timurids, had a significant influence on Azerbaijani literature in the XVI and XVII centuries. The fact that the poet's language was easily understood by many Turkic people at that time and the philanthropy, deep meaning and high art example in his poems caused his works to spread in a wide geography – all over Turkestan, as well as in Azerbaijan, Iran, Turkey and India. In this article, scholars' such as Fuad Köprülü, E. Gibb, Ali Nihat Tarlan, Mehmed Çavuşoğlu, Ahmed Caferoğlu, E. Demircizade, Roza Eyvazova, Cennet Nağıyeva, Jale Demirci, Paşa Kerimov, Almaz Ülvî’s research on the history of bringing the literary heritage of Alisher Navoi to Azerbaijan and the influence of Navoi's works on the works of Azerbaijani poets has been comparatively analyzed. In addition, it has been learned that poets such as Kishveri, Fuzuli, Sadik Bey Sadiki, Muhammed Amani, Shah Ismail Hatai, Rahmeti Tebrizi, Saib Tebrizi, Alijan Kovsi Tebrizi, Zafer Murtazakuluhan Shamli and Vahidi Kazvini wrote nazira, mukhammas and tazkiras by being influenced by the poems of Alisher Navoi in Azerbaijan.